A inteligência artificial no campo ciência, tecnologia e sociedade: um estudo comparativo entre indicadores da produção científica - Groenner, Luciana Castro (2024)
We are witnessing a moment of significant technological change, where the tools and applications derived from Artificial Intelligence (AI) have been generating consequences in the individual and collective sphere. This area of science is branched into other fields, producing technologies increasingly used by industries, governments, and individuals. This work investigated how AI research is taking place, with a special interest in identifying research in the field of Science, Technology and Society (STS) on AI, from publications in the Web of Science (WoS). The methodology employed involved quantitative analysis, through bibliometrics, to map where research is taking place that develops AI tools and applications, as well as to identify which fields of knowledge are involved in this discussion, with the intention of locating STS in this debate. Qualitative research was also carried out, to review the literature that addresses AI and STS, to weave together the discussions developed complemented by a content analysis of the articles retrieved in the WoS, on AI, in the field of STS. The results allowed us to identify how AI research is taking place in Brazil and in the world, to discover that the STS field is critically debating the consequences of this technological change, however, it is still an initial discussion, especially in Brazil, with the potential to be scaled up. It was demonstrated that STS can contribute significantly to ensuring that, in Brazil, the issues involving AI can be critically debated to build alternatives where these technologies are developed and absorbed, mitigating the resulting problems.